PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN TERHADAP KINERJA INDIVIDU KARYAWAN DI PT. MAKASSAR TENE - Herlin Saputri, A. Febri Wulandari; Hasan, Asriani; Nurhidayah, Nurhidayah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study aims to analyze the effect of sales accounting information systems on individual employee performance. The method used is quantitative research with data collection through questionnaires distributed to 35 employees in the company. The results of the study indicate that the sales accounting information system has a significant effect on individual employee performance, with a significance value of 0.002 which is smaller than 0.05 and a t-count value of 3.329 which is greater than the t table of 1.692. These findings support the hypothesis that the implementation of a more effective accounting information system can improve employee performance. This study also strengthens the theory of the Technology Acceptance Model (TAM) and the Theory of Reasoned Action (TRA), which show the importance of perceived usefulness and ease of use of information systems in improving work productivity.